Self-Modifying Nanointerface Driving Ultrahigh Bidirectional Thermal Conductivity Boron Nitride-Based Composite Flexible Films - Huang, Taoqing; Zhang, Xinyu; Wang, Tian; Zhang, Honggang; Li, Yongwei; Bao, Hua; Chen, Min; Wu, Limin (Nano-Micro Letters, 2022)
While boron nitride (BN) is widely recognized as the most promising thermally conductive filler for rapidly developing high-power electronic devices due to its excellent thermal conductivity and dielectric properties, a great challenge is the poor vertical thermal conductivity when embedded in composites owing to the poor interfacial interaction causing severe phonon scattering. Here, we report a novel surface modification strategy called the “self-modified nanointerface” using BN nanocrystals (BNNCs) to efficiently link the interface between BN and the polymer matrix. Combining with ice-press assembly method, an only 25 wt% BN-embedded composite film can not only possess an in-plane thermal conductivity of 20.3 W m−1 K−1 but also, more importantly, achieve a through-plane thermal conductivity as high as 21.3 W m−1 K−1, which is more than twice the reported maximum due to the ideal phonon spectrum matching between BNNCs and BN fillers, the strong interaction between the self-modified fillers and polymer matrix, as well as ladder-structured BN skeleton. The excellent thermal conductivity has been verified by theoretical calculations and the heat dissipation of a CPU. This study provides an innovative design principle to tailor composite interfaces and opens up a new path to develop high-performance composites. Highlights: 1 The flexible composite film presents ultrahigh thermal conductivity and good thermal management performance in electronic devices. 2 An original “self-modified nanointerface” strategy is used to reduce the interfacial thermal resistance between boron nitride and the polymer matrix. 3 The ideal phonon spectrum matching between boron nitride nanocrystals and fillers as well as the strong interaction between self-modified fillers and the polymer matrix are the two major contributors to decrease the interfacial thermal resistance.